2023
DOI: 10.3390/metabo13020158
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Heavy Metals and Serum Adiponectin Levels among Workers: A 2-Year Follow-Up Study

Abstract: The workers exposed to metal fumes had an increased risk of metabolic syndrome, which was correlated with decreased serum adiponectin. Thus, we aimed to explore whether heavy metal exposure affects the adiponectin level. There were 96 male workers recruited from a shipyard at baseline. Apart from 82 participants completed the follow-up assessments, new participants were recruited in next year. Finally, there were 100 welding workers in the exposure group and 31 office workers in the control group. Inferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a study conducted on welders in Canada, the prevalence of pre-obesity and obesity was 61% [20]. In Taiwan, welders' average body mass index was 25.2 [21]. In the United States, pre-obesity prevalence among workers was 36.1%, obesity was 22.0%, and the mean body mass index was 26.2.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on welders in Canada, the prevalence of pre-obesity and obesity was 61% [20]. In Taiwan, welders' average body mass index was 25.2 [21]. In the United States, pre-obesity prevalence among workers was 36.1%, obesity was 22.0%, and the mean body mass index was 26.2.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have investigated the relationship between Pb or Cd and serum adiponectin. An occupational study of 100 welding workers in Taiwan found that those with higher urinary levels of heavy metals, including Pb and Cd, had lower levels of serum adiponectin, suggesting that Pb exposure may be the main contributor to this association [21]. However, studies on the general population have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have consistently indicated that exposure to high doses of Pb or Cd can adversely impact adiponectin levels [19,20]. Moreover, an occupational study involving welders exposed to heavy metals, including Pb and Cd, also reported lower levels of serum adiponectin [21]. However, research on the association between Pb or Cd exposure and adiponectin levels in the general population remains limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%